Biomass-mediated synthesis of Cu-doped TiO2 nanoparticles for improved-performance lithium-ion batteries - Kashale, Anil A.; Dwivedi, Pravin K.; Sathe, Bhaskar R.; Shelke, Manjusha V.; Chang, Jia-Yaw; Ghule, Anil V. (ACS Omega, 2018)
Pure TiO2 and Cu-doped TiO2 nanoparticles are synthesized by the biomediated green approach using the Bengal gram bean extract. The extract containing biomolecules acts as capping agent, which helps to control the size of nanoparticles and inhibit the agglomeration of particles. Copper is doped in TiO2 to enhance the electronic conductivity of TiO2 and its electrochemical performance. The Cu-doped TiO2 nanoparticle-based anode shows high specific capacitance, good cycling stability, and rate capability performance for its envisaged application in lithium-ion battery. Among pure TiO2, 3% Cu-doped TiO2, and 7% Cu-doped TiO2 anode, the latter shows the highest capacity of 250 mAh g(-1) (97.6% capacity retention) after 100 cycles and more than 99% of coulombic efficiency at 0.5 A g(-1) current density. The improved electrochemical performance in the 7% Cu-doped TiO2 is attributed to the synergetic effect between copper and titania. The results reveal that Cu-doped TiO2 nanoparticles might be contributing to the enhanced electronic conductivity, providing an efficient pathway for fast electron transfer.

Thermally constructed stable Zn-doped NiCoOx-z alloy structures on stainless steel mesh for efficient hydrogen production via overall hydrazine splitting in alkaline electrolyte - Kashale, Anil Ashok; Rasal, Akash Sanjay; Hsu, Fei-Chien; Chen, ChangChun; Kulkarni, Sayali Nitin; Chang, Chun Hao; Chang, Jia-Yaw; Lai, Yuekun; Chen, I. -Wen Peter (Journal of Colloid and Interface Science, 2023)
Hydrogen has a high energy density of approximately 120 to 140 MJ kg(-1), which is very high compared to other natural energy sources. However, hydrogen generation through electrocatalytic water splitting is a high electricity consumption process due to the sluggish oxygen evolution reaction (OER). As a result, hydrogen generation through hydrazine-assisted water electrolysis has recently been intensively investigated. The hydrazine electrolysis process requires a low potential compared to the water electrolysis process. Despite this, the utilization of direct hydrazine fuel cells (DHFCs) as portable or vehicle power sources necessitates the development of inexpensive , effective anodic hydrazine oxidation catalysts. Here, we prepared oxygen-deficient zinc-doped nickel cobalt oxide (Zn-NiCoOx-z) alloy nanoarrays on stainless steel mesh (SSM) using a hydrothermal synthesis method followed by thermal treatment. Furthermore, the prepared thin films were used as electrocatalysts , the OER and hydrazine oxidation reaction (HzOR) activities were investigated in three-and two-electrode systems. In a three-electrode system, Zn-NiCoOx-z/SSM HzOR requires-0.116 V (vs RHE) potential to achieve a 50 mA cm(-2) current density, which is dramatically lower than the OER potential (1.493 V vs RHE). In a two-electrode system (Zn-NiCoOx-z/SSM(-)IIZn-NiCoOx-z/SSM(+)), the overall hydrazine splitting potential (OHzS) required to reach 50 mA cm(-2) is only 0.700 V, which is dramatically less than the required potential for overall water splitting (OWS). These excellent HzOR results are due to the binder-free oxygen-deficient Zn-NiCoOx-z/ SSM alloy nanoarray, which provides a large number of active sites and improves the wettability of cat-alysts after Zn doping. (C) 2023 Elsevier Inc. All rights reserved.
Keywords: Hydrazine Oxidation Reaction; hydrogen evolution reaction; Oxygen Evolution Reaction; Oxygen-Deficient Materials; Zinc Doping